Development of a High-Throughput Screening Approach to Identify Production Enhancers of Adeno-Associated Virus - Maznyi, Glib (Université d'Ottawa / University of Ottawa, 2023)
Gene therapy has emerged as a revolutionary approach for treating genetic disorders, holding great promise for improving patient outcomes. Among the various viral vectors used for delivery of therapeutic transgenes, Adeno-Associated Viruses (AAVs) have gained prominence due to their favorable characteristics including low immunogenicity, long-term gene expression, and the ability to target both dividing and non-dividing cells. However, AAV’s are associated with the high costs of production and challenges with production of a high-quality virus, limiting AAV’s utilization and widespread use. In this study, we aimed to develop a high-throughput screening assay targeting AAV production enhancers, thus addressing the manufacturing obstacles and advancing the affordability and accessibility of gene therapies. To help overcome the limitations and expenses associated with AAV manufacturing, an innovative high-throughput screening assay was developed with the intent to identify cell culture additives/conditions which maximize AAV production. We optimized various parameters, including the transgene, producer and reporter cell lines, harvest timings and methods, and transduction techniques. The optimized screening assay was employed to evaluate novel compounds across several timings of addition, for their ability to enhance AAV production. Notably, several compounds indicated transfection enhancing capabilities up to 3.4-fold and the developed assays final variability was below 14%. Additionally, compound combinations were assessed to uncover potential additive and synergistic effects that could further enhance AAV productivity. In conclusion, our study presents a significant advancement in targeting the manufacturing challenges associated with AAV. By utilizing an optimized high-throughput screening assay, researchers and manufacturers can identify compounds that enhance AAV production, paving the way for cost-effective and scalable manufacturing processes. Ultimately, this progress holds the potential to improve the affordability, accessibility, and impact of gene therapies for patients worldwide.
Keywords: Adeno-Associated Virus; High-thgoughput screening; Drug Discovery